ANALISIS KEMAMPUAN NUMERASI SISWA PADA PEMBELAJARAN MATEMATIKA KELAS III DI SDN BRAJI - Adim, Moh; Yuli Mestika D, Ike; Bahri, Syaiful (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the numeracy ability of grade III students at SDN Braji in understanding mathematical concepts and their application in solving everyday problems. The research method used is descriptive qualitative, with data collection techniques through observation, interviews, and documentation with class teachers. The results of the study showed that the level of student attention numeracy ability was low, with some students showing poor understanding of the concept of numbers and arithmetic operations, the learning methods used by teachers, and support from the learning environment. It can be concluded that the numeracy ability of lower grade students in arithmetic operations material has a low level of numeracy ability, where there are 3 numeracy indicators that often appear at each level of Students' abilities can be divided into several indicators. First, students are able to use various numbers from 1 to 100 related to basic mathematics to solve problems in various contexts of everyday life. The second indicator is that students are able to analyze information presented in various forms of problems, the third is that students are able to answer questions correctly in the form of stories. this only appears in students who have a high level of numeracy ability